Komitmen Organisasi sebagai Mediasi Pengaruh Pengembangan Karir terhadap Kinerja - putu purnawati; Anak Agung Dwi Widyani; Ni Putu Risma Devy (Widya Manajemen, 2021)
An achievement that is achieved by a person in carrying out his duties based on ability, experience, and seriousness, and time. So that CV. Bali Villa Construction can continue to exist in competition, so the company must have quality human resources. The purpose of this study was to determine the effect of career and organizational commitment on employee performance, the effect of career development on commitment, and organizational commitment as mediation for career development on employee performance. The number of samples used was 45 people using the census method. Data collection using a questionnaire. The data analysis technique used SEM-PLS. The results showed that career development and organizational commitment have a positive effect on employee performance. Career development has a positive effect on employee performance. Organizational commitment can mediate the influence of career on employee performance.